Strategic interactions in U.S. monetary and fiscal policies - Xiaoshan Chen; Eric M. Leeper; Campbell B. Leith (Quantitative Economics, 2022)
We estimate a model in which fiscal and monetary policy obey the targeting rules of distinct policy authorities, with potentially different objective functions. We find: (1) Time-consistent policy fits U.S. time series at least as well as instrument-rules-based behavior; (2) American policies often do not conform to the conventional mix of conservative monetary policy and debt-stabilizing fiscal policy, although economic agents expect fiscal policy to stabilize debt eventually; (3) Even after the Volcker disinflation, policies did not achieve that conventional mix, as fiscal policy did not begin to stabilize debt until the mid 1990s; (4) The high inflation of the 1970s could have been effectively mitigated by either a switch to a fiscal targeting rule or an increase in monetary policy conservatism; (5) If fiscal behavior follows its historic norm to eventually stabilize debt, current high debt levels produce only modest inflation; if confidence in those norms erodes, high debt may deliver substantially more inflation.
Keywords: C11; E31; E63; 330; Bayesian estimation; monetary and fiscal policy interactions; targeting rules; Markov switching